Developing students’ hand hygiene behaviors in a primary school from Turkey: A school-based health education study - Sibel Cevizci,; Aysegul Uludag,; Naci Topaloglu,; Ulken Tunga Babaoglu,; Merve Celik,; Coskun Bakar, (Universiti Kebangsaan Malaysia, 2015)
Background: Hand hygiene is a cheap, simple, and an effective method that is necessarily implemented in crowded areas such as schools where infectious diseases can spread easily. Objective: To improve hand hygiene of students from grade 6 to 8 in a primary school from Canakkale, Turkey. Materials and Methods: This research was conducted in the educational year of 2012–2013 in a primary school, Kepez, Canakkale, Turkey. The subjects consisted of 185 primary school students from grade 6 to 8. Of these, 161 (participation rate = 87%) students participated. It was an educational study devoted to improve skills about hand hygiene. This study was carried out in three steps. First, a self-answered questionnaire and a standard checklist were used before hand hygiene training. Second, after 1 week from this first step, students were trained for improving hand-washing skills. Immediately afterward the training course, researchers observed each student for the assessment of their hand-washing habits and then filled the skill checklist. The last evaluation was made in the third step after 3 months from the training course. Students’ hand-washing skill scores before and after the training were compared. Statistical analyses were performed using the SPSS software, version 19.0. A p-value of less than 0.05 was considered to be statistically significant. Results: Of 161 participants, 50.1% were boys and 49.0% were girls with the mean age of 12.6 ± 0.9 (min 11; max 14) years. Of these participants, 32.3% were from grade 6, 32.3% from grade 7, and 35.4% from grade 8; 98.1% students were living in Kepez and 1.9% were living in village. A statistically significant difference was detected between the first practice, which was made before training, and the second and third practices, which were made after training, in terms of handwashing skill development (p o 0.001). After the training, hand-washing skill scores showed a significant increase than before-training skill scores in both female and male students (p o 0.001). Conclusion: In this study, hand-washing skill training was found to be effective. In addition, students were found to be successful on implementing hand-washing skills in the last practice that was done after 3 months from the training course. However, it should be considered that newly acquired behaviors must be followed once in 6 months or in a year with continuity for these behaviors to be permanent and long standing.